Uterine Artery Embolization Combined with Local Methotrexate and Systemic Methotrexate for Treatment of Cesarean Scar Pregnancy with Different Ultrasonographic Pattern - Lian, Fan; Wang, Yu; Chen, Wei; Li, Jiaping; Zhan, Zhongping; Ye, Yujin; Zhu, Yunxiao; Huang, Jia; Xu, Hanshi; Yang, Xiuyan; Liang, Liuqin; Yang, Jianyong (Cardiovascular and interventional radiology, 2012)
Purpose This study was designed to compare the effectiveness of systemic methotrexate (MTX) with uterine artery embolization (UAE) combined with local MTX for the treatment of cesarean scar pregnancy (CSP) with different ultrasonographic pattern, and to indicate the preferable therapy in CSP patients. Methods The results of 21 CSP cases were reviewed. All subjects were initially administrated with systemic MTX (50 mg/m 2 body surface area). UAE combined with local MTX was added to the patients who had failed systemic MTX. The transvaginal ultrasonography data were retrospectively assessed, and two different ultrasonographic patterns were found: surface implantation and deep implantation of amniotic sac. The management and its effectiveness for patients with the two ultrasonographic patterns were studied retrospectively. Ultrasound scan and serum β-hCG were monitored during follow-up. Data were analyzed with the Student’s t test. Results Nine patients were successfully treated with systemic MTX. The remaining 12 cases were successfully treated with additional UAE combined with local MTX. According to the classification by Vial et al. of CSP on ultrasonography, most surface implanted CSPs (8/11, 72.7%) could be successfully treated with systemic MTX, whereas most deeply implanted CSPs (9/10, 90%) had failed systemic MTX but still could be successfully treated with additional UAE combined with local MTX. All patients recovered without severe side effects. Most patients with a future desire for reproduction achieved subsequent pregnancy. Conclusions For CSP patients suitable for nonsurgical treatment, UAE combined with local MTX would be the superior option compared with systemic MTX in the cases with deep implantation of amniotic sac.